Detecção e classificação molecular de Chlamydophila psittaci em amostras fecais de aves assintomáticas - Braz, M.a. [UNESP]; Silva, D.c. [UNESP]; Santiago, M.e.b. [UNESP]; Garcia, S.d. [UNESP]; Nakamura, A.a. [UNESP]; Meireles, Marcelo Vasconcelos [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2014)
Chlamydophila psittaci is a bacterium that causes respiratory or systemic disease in birds and humans. Owing to the risk of transmission from asymptomatic birds to humans, the objective of this study was to detect the presence of Chlamydophila spp. in asymptomatic birds. Four hundred and three fecal samples or cloacal swabs were collected from domestic, wild or exotic birds. The 403 samples were examined by real time PCR specific for the 16S subunit of rRNA gene using SsoFastEvaGreen®SupermixTM (Bio-Rad) and melting curve analysis. Hemi-nested PCR specific for the OMP-A gene, accomplished in real-time PCR positive samples, was followed by sequencing of the amplified fragments to determine the genotype of C. psittaci. Real-time PCR was positive in 17 (4.21%) samples. Hemi-nested PCR revealed positivity in two samples previously positive by real-time PCR. Sequencing of the fragment amplified by hemi-nested PCR allowed for the identification of genotype A of C. psittaci in one sample. The results of this experiment show that the real-time PCR targeting the 16S rRNA gene followed by melting curve analysis can be used for diagnosis of Chlamydophila sp. in fecal samples of asymptomatic birds. The classification of the Chlamydophila species and the genotype of C. psittaci must be accomplished by PCR targeting the ompA gene and sequencing of the amplified fragments.

Chlamydophila psittaci é uma bactéria que causa doença respiratória ou sistêmica em aves e em seres humanos. Em vista do risco de transmissão para humanos, o objetivo deste estudo foi detectar a presença de Chlamydophila spp. em amostras de fezes ou suabes cloacais de aves assintomáticas. Foram colhidas 403 amostras fecais ou suabes cloacais, provenientes de aves domésticas, selvagens ou exóticas. As amostras foram submetidas à PCR em tempo real para C. psittaci, para amplificação de fragmento parcial do gene da subunidade 16S do rRNA, utilizando o SsoFastTM EvaGreen® Supermix (Bio-Rad) e análise da curva de dissociação. Para determinação do genótipo de C. psittaci, foi usada a hemi-nested PCR visando à amplificação de fragmento parcial do gene OMP-A, realizada nas amostras positivas pela PCR em tempo real, seguida de sequenciamento dos fragmentos amplificados. A PCR em tempo real revelou positividade em 17 (4,21%) amostras. A hemi-nested foi positiva em 2 amostras positivas pela PCR em tempo real. O genótipo A de C. psittaci foi identificado pelo sequenciamento de uma amostra amplificada pela hemi-nested PCR. Os resultados deste experimento demonstram que a PCR em tempo real, visando à amplificação de fragmento parcial da subunidade 16S do rRNA, seguida da análise da curva de dissociação, pode ser utilizada para detecção de DNA de Chlamydophila sp. em amostras fecais de aves assintomáticas. A classificação da espécie de Chlamydophila e do genótipo de C. psittaci deve ser realizada por meio de PCR tendo como alvo o gene ompA e sequenciamento dos fragmentos amplificados.
Detection and molecular characterization of Chlamydophila psittaci in asymptomatic birds
Keywords: aves; psitacose; diagnóstico molecular; zoonoses; birds; psittacosis; molecular diagnostic; zoonoses